Pengembangan Aplikasi SIZISKU 1.0 Untuk Meningkatkan Optimalisasi Pengelolaan Lembaga Zakat Nasional (UIN Sunan Kudus, 2019)
The potential of receiving zakat, infak and alms in Indonesia is quite large. That is because the majority of Indonesia's population is Moslem, reaching 207.2 million people (BPS, 2017). On the other hand, the number of poor people in Indonesia is also quite alarming, reaching 27.77 million people (BPS, 2017). Therefore, it is expected that the potential of receiving zakat, infak and alms can be managed as well as possible so that the benefits can be optimal as a counterweight to the country's economic sector. This paper aims to present the idea of an android-based application development product named SIZISKU. This application is a new idea that aims to improve the optimization of zakat, infak and alms management by integrating national zakat institutions. By integrating national zakat institutions in an integrated application, the mustahik (the receivers of zakat, infak, and alms) database of all zakat institutions can be collected. By that way, it can avoid overlapping zakat recipients from the same institution. It also makes the distribution of zakat, donations and alms can be delivered equally. In addition, the purpose of this paper is to find out what the stages to develop the application and who are the parties involved to implement it. The result of this writing is the prototype of the SIZISKU application.